Meta‐analysis of chromosome‐scale crossover rate variation in eukaryotes and its significance to evolutionary genomics. Issue 11 (23rd May 2018) - Haenel, Quiterie; Laurentino, Telma G.; Roesti, Marius; Berner, Daniel
Abstract: Understanding the distribution of crossovers along chromosomes is crucial to evolutionary genomics because the crossover rate determines how strongly a genome region is influenced by natural selection on linked sites. Nevertheless, generalities in the chromosome‐scale distribution of crossovers have not been investigated formally. We fill this gap by synthesizing joint information on genetic and physical maps across 62 animal, plant and fungal species. Our quantitative analysis reveals a strong and taxonomically widespread reduction of the crossover rate in the centre of chromosomes relative to their peripheries. We demonstrate that this pattern is poorly explained by the position of the centromere, but find that the magnitude of the relative reduction in the crossover rate in chromosome centres increases with chromosome length. That is, long chromosomes often display a dramatically low crossover rate in their centre, whereas short chromosomes exhibit a relatively homogeneous crossover rate. This observation is compatible with a model in which crossover is initiated from the chromosome tips, an idea with preliminary support from mechanistic investigations of meiotic recombination. Consequently, we show that organisms achieve a higher genome‐wide crossover rate by evolving smaller chromosomes. Summarizing theory and providing empirical examples, we finally highlight that taxonomically widespread and systematic heterogeneity in crossover rate along chromosomes generates predictable broad‐scale trends in genetic diversity and population differentiation by modifying the impact of natural selection among regions within a genome. We conclude by emphasizing that chromosome‐scale heterogeneity in crossover rate should urgently be incorporated into analytical tools in evolutionary genomics, and in the interpretation of resulting patterns.